Centennial-scale climate variability and human land-use shaped vegetation and lake dynamics in southern Spain over the past three millennia - Gonzalo Jiménez-Moreno; Erik J. de Boer; Jon Camuera; Antonio García-Alix; Fernando Gázquez; Aurora Castillo-Baquera; Lucía Martegani; Miguel Rodríguez-Rodríguez; Marta Rodrigo-Gámiz; Francisco J. Jiménez-Espejo; Lu Chenao; José S. Carrión (Anthropocene, 2026)

New extensions of Cell2Fire software for fire risk analysis and evaluation in Chilean forests - Jaime Carrasco-Barra; José Ramón González-Olabarria; Camilo Matus-Olivares; Felipe Ulloa-Fierro; Felipe Soto; David Palacios; Rodrigo Mahaluf; Felipe de la Barra; Carolina Espinoza; Matías Vilches; Matilde Rivas; Fernando Badilla; et al. (Environmental Modelling & Software, 2026)

Spectrum of DNA Variants Underlying Deafness in an Ecuadorian Cohort - Anghela Reinoso-Castillo; Memoona Ramzan; Andrea Carrera-Gonzalez; Christian Rivas-Iglesias; Stefanny Montufar; Rodrigo Vinueza-Gavilanes; Carson Smith; Arianne Llamos-Paneque; Mustafa Tekin (Biochemical Genetics, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Genotoxicity and oral tissue damage associated with tooth bleaching agents: A scoping review - Patrick Wesley Marques de Boa; Mariana Silva de Bessa; Flávio Pereira dos Santos Filho; Lara Beatriz Nascimento Diniz; Rodrigo Othávio de Assunção e Souza; Laércio Almeida de Melo; Arthur Cesar de Medeiros Alves; Boniek Castillo Dutra Borges (Mutation Research - Reviews in Mutation Research, 2026)

Microbial communities and pharmaceutical contaminants in the water-soil–plant continuum of sugarcane crops irrigated with contaminated waters from the Cauca River Valley, Colombia - Juan Ceballos-Castillo; Rodrigo A. Echeverry-Gallego; Diana Martínez-Pachón; Alejandro Moncayo-Lasso; Javier Vanegas (Environmental Science and Pollution Research, 2026)
“Agricultural irrigation with contaminated water poses a major risk to food security and public health. This study examined contaminant transfer across the water–soil–plant continuum in sugarcane crops irrigated with water from the Cauca River, Colombia. Microbial community composition was characterized using 16S rRNA gene sequencing, while pharmaceutical active compounds (PhACs) in irrigation water and sugarcane plants were quantified by UHPLC–MS/MS. Microbial analyses revealed a potential biological pathway of microorganisms from water and soil into plant endophytic tissues. Bacterial diversity decreased markedly, from more than 400 genera identified in water and soil to only 64 genera detected within endophytic tissues. Nine potentially pathogenic genera-including Escherichia–Shigella , Pseudomonas , and Bacillus - were found across all matrices, suggesting microbial internalization. Bioinformatic predictions indicated the presence of genes associated with virulence traits (e.g., antimicrobial resistance and biofilm formation) as well as beneficial functions such as nitrogen fixation and phosphate solubilization. In parallel, high concentrations of PhACs were detected in irrigation water, including valsartan (up to 1309 ng L⁻ 1 ) and diclofenac (up to 969 ng L⁻ 1 ), whereas none or only low concentration detected in sugarcane tissues. Overall, the primary risk to human health appears to stem not from chemical uptake but from microbial infiltration shaped by environmental pressures. Therefore, managing plant-associated microbiomes is essential to mitigate health risks while harnessing biotechnological potential for sustainable agriculture.”

Zinc deficiency and sarcopenia define a metabolic frailty phenotype predicting hepatic encephalopathy and early mortality in cirrhosis - Osvely Méndez-Guerrero; Anaisa Carranza-Carrasco; Rodrigo Guerrero-Guerrero; Lilia Castillo-Martínez; Fabiola M. Del Razo-Olvera; Liliana Juárez-Martínez; Rodrigo Otero-Otero; Alma Estanes-Hernández; Patricia Clark; Carlos A. Aguilar-Salinas; Aldo Torre; Graciela E. Castro-Narro; et al. (Metabolic Brain Disease, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Geophysical Modeling of Complex Karst Features in the Yucatán Peninsula - José Carlos Ortíz-Alemán; Rodrigo Negrete-Juarez; Jaime Urrutia-Fucugauchi; Mauricio Orozco-del-Castillo; Julian Zapotitla-Roman; Sebastian López-Juárez (Pure and Applied Geophysics, 2026)

Spatio-temporal performance of 2D local inertial hydrodynamic models for urban drainage and dam-break applications - Marcus N. Gomes Jr.; Maria A.R.A. Castro; Luis M.R. Castillo; Mateo H. Sánchez; Marcio H. Giacomoni; Rodrigo C.D. de Paiva; Paul D. Bates (Journal of Hydrology, 2026)

Metabolic and productive responses to heat stress in transition dairy cows: Interactions with calving stage, season, and farm management - E. N. Martínez; C. Castillo; L. Avendaño Reyes; Rodrigo Muiño; L. Díaz-González; J. L. Benedito; J. Hernández (International Journal of Biometeorology, 2026)
This study investigated the effects of heat stress (HS), calving period, and farm-level management on the metabolic and productive responses of transition dairy cows. Conducted on three commercial farms in northwestern Spain, the study employed a multifactorial design across two seasons (winter and summer) and four peripartum time points. Biochemical parameters, including non-esterified fatty acid (NEFA), β-hydroxybutyrate (BHB), urea, total protein, albumin, glucose, gamma-glutamyltransferase (GGT), and aspartate aminotransferase (ASAT) were analyzed using repeated-measures MANOVA. No significant three-way interactions were found, but several two-way interactions emerged. Notably, NEFA and urea levels varied significantly between farms, while total protein and albumin were influenced by both partum stage and season. Elevated NEFA and BHB concentrations postpartum indicated intensified lipid mobilization and negative energy balance, exacerbated under HS. Reduced albumin and increased urea levels suggested hepatic stress and altered protein metabolism. Farm-specific differences in ASAT during summer highlighted the role of local environmental and management conditions. These findings underscore the complex interplay between physiological stage, environmental stressors, and farm practices. Tailored intervention (such as nutritional adjustments, cooling systems, and precision monitoring) are essential to mitigate the metabolic burden of HS and safeguard cow health and productivity. Future research should explore long-term impacts and adaptive strategies across diverse production systems.

Infrared Emission in the Second Biological Window in LaInO3:Ho3+ Exciting in the First Biological Window - Mauricio A. Vega-Pallauta; Rodrigo Castillo; Kevin Soler-Carracedo; Inocencio R. Martin (Journal of Fluorescence, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Climate dynamics during the last 3000 years forced environmental and sedimentation changes in southern Spain: The Laguna Grande de Archidona record - Gonzalo Jiménez-Moreno; Antonio García-Alix; Fernando Gázquez; Aurora Castillo-Baquera; Lucía Martegani; Miguel Rodríguez-Rodríguez; Marta Rodrigo-Gámiz; Francisco J. Jiménez-Espejo (CATENA, 2025)

Pathogenic impact of Vibrio spp. in scallop hemolymph: Implications for health in aquaculture - Roxana González; Mauricio Peña-Jaña; Rodrigo Rojas; Daniel Oyanedel; Carlos Henríquez-Castillo; Orlando Astudillo; Paulina Schmitt; Katherina Brokordt (Aquaculture, 2025)

Effect of long-term retrogradation on the crystallinity, vibrational and rheological properties of potato, corn, and rice starches - Gonzalo Velazquez; Cristian Felipe Ramirez-Gutierrez; Guadalupe Mendez-Montealvo; Rodrigo Velazquez-Castillo; Luis Fernando Morelos-Medina; Eduardo Morales-Sánchez; Marcela Gaytán-Martínez; Mario E. Rodríguez-García; Brenda Contreras-Jiménez (Food Chemistry, 2025)

Modeling and scenario building for climate change adaptation planning: The case of large mining in Chile - Rodrigo Jiliberto Herrera; Rodrigo Ramos-Jiliberto; Emilio Castillo Dintrans; Angel Allendes Caro; Luis Felipe Orellana Espinoza; Marco Billi; Marcelo Ramírez Valenzuela (Environmental Development, 2024)

How do the BRICS approach sustainable concerns? A systematic literature review - Cleiton Hluszko; Diego Alexis Ramos Huarachi; Micaela Ines Castillo Ulloa; Rodrigo Salvador; Fabio Neves Puglieri; Antonio Carlos de Francisco (Environmental Development, 2024)

Metal (loid) Exposure and Overweight and Obesity in 6–12-Year-Old Spanish Children - Inmaculada Salcedo-Bellido; Helga Castillo Bueno; Pablo Olmedo; Fernando Gil; Francisco M. Ocaña-Peinado; Lourdes Rodrigo; Ana Rivas (Exposure and Health, 2024)
Epidemiological studies focusing on metal(oid) exposure and excess body weight among children show inconsistent results and the influence of metal(loid) mixtures has been little studied. We aimed to explore the effect of 10 metal(loid)s, individually and in combinations, on overweight and obesity among children aged 6–12. Urinary levels of these metal(oid)s from 92 controls and 51 cases with overweight and obesity were analyzed. Metal(loid) levels were log-transformed and categorized into tertiles according to the control group cutoff points. Two logistic regression models and weighted quantile sum regressions (WQS) were run: model 1 adjusting for age, sex, creatinine, energy intake and physical activity and model 2 additionally adjusting for maternal education, rice and fish consumption. In the single metal(oid) exposure model, there was a trend of significant negative association for urinary cobalt (Co), where children in the third tertile had lower odds of present overweight and obesity than those in the first (Odds Ratio, OR = 0.43; 95% Confidence Interval, CI = 0.20–0.93). Urinary chromium (Cr) levels were borderline-significant negatively associated with overweight and obesity (ORa = 1.70; 95% CI = 0.97–2.98). Molybdemun, Cr and Co had a major contribution to the inverse association between metal(loid) mixture and overweight and obesity as well as lead, cadmium and total arsenic in the positive relationship. Our findings in this explorative study suggested an inverse association of high urinary Co levels with overweight and obesity. Moreover, metal(loid) mixture exposure may have influence on overweight and obesity with an important contribution of Co in the potential negative effect.

Long-term substitution of fish oil with alternative sources in Atlantic salmon (Salmo salar): Performance, health, and consumer appeal - Tomás Pablo Leyton; Sandra Marín; Sergio Castillo; Rodrigo Sánchez; Rayen Collipal; Jorge Madrid; Ana Farías (Aquaculture, 2024)

Development and characterization of a novel variant of long-acting bovine follicle-stimulating hormone (brscFSH) - Oscar Ignacio Cabeza; Natalie Parra; Rita Cerro; Rodrigo Mansilla; Roxana Zuniga Sanchez; Miguel Gutierrez-Reinoso; Eduardo H. Escribano; Raul Castillo; Lleretny Rodriguez-Alvarez; Kaio Tavares; Saul Gaudencio; Leonardo Martins; et al. (Theriogenology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Evidence of forestry management and arboriculture practices in waterlogged wood remains from three wells at the Roman and late antiquity sites of Iesso and Vilauba (Catalonia, Spain) - Eva Maria López Castillo; Oriol López-Bultó; Anna Berrocal Barberà; Pere Castanyer Masoliver; Joaquim Pera Isern; Esther Rodrigo Requena; Raquel Piqué Huerta (Quaternary International, 2024)

Influence of human emotions on conservation attitudes toward relevant wildlife species in El Triunfo Biosphere Reserve, Mexico - Nathalia M. Castillo-Huitrón; Eduardo J. Naranjo; Dídac Santos-Fita; Mateo Peñaherrera-Aguirre; Pavol Prokop; Rodrigo Cisneros; Silvia Vaca Gallegos; Zuzana Ježová (Biodiversity and Conservation, 2024)

Terrestrial and Martian space weather: A complex systems approach - Abraham Chian; Rodrigo Miranda; Cesar Bertucci; Xóchitl Blanco-Cano; Joe Borovsky; Sergio Dasso; Ezequiel Echer; Adriane Franco; Kirolosse M. Girgis; J. Américo González-Esparza; Tohru Hada; Hiroshi Hasegawa; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Re-evaluating the link between the Ellsworth Mountains and East Antarctica in the Neoproterozoic: Implications for the breakup of Rodinia and the existence of Pannotia - Paula Castillo; Fernando Poblete; Rodrigo Fernández; Joaquín Bastías-Silva; C. Mark Fanning (Precambrian Research, 2024)

The importance of assets for coping with COVID-19 and other shocks - Julio A. Berdegué; María J. Castillo; Ileana Gómez; Gustavo Gordillo; José Navea; Irvin Rojas; Rodrigo Yáñez (Global Food Security, 2024)

Phosphorus recovery from domestic wastewater: A review of the institutional framework - Valentina Carrillo; Rodrigo Castillo; Albert Magrí; Eduardo Holzapfel; Gladys Vidal (Journal of Environmental Management, 2024)

Influence of Krill Meal on the Performance of Post-Smolt Atlantic Salmon That Are Fed Plant-Based and Animal-Based Fishmeal and Fish Oil-Free Diets - Frederick T. Barrows; Kelly B. Campbell; T. Gibson Gaylord; Rodrigo C. M. Sanchez; Sergio A. Castillo; Ewen McLean (Fishes, 2023)
The purpose of this study was to determine the influence of krill meal (KM) inclusion at various levels (0%, 2.5%, 5%) in plant-based and animal-based feeds, that were fishmeal (FM) and fish oil (FO) free, on Atlantic salmon growth. A FM/FO feed containing 0% KM was the control. Using a 2 × 3 factorial approach, diets were randomly assigned to one of 28 0.5 m3 flow-through tanks (n = 4 tanks per diet) initially stocked with 60 fish (148.4 ± 12.9 g; 23.6 ± 0.8 cm; condition factor (K) = 1.16 ± 0.08) each. Salmon were fed for 90 days using automatic feeders ad libitum. On day 45, stocking densities were reduced to 45 fish per tank by the random removal of 15 individuals to remove any potential of density affecting growth through the trial end. Water temperature, oxygen saturation, pH, and salinity throughout the trial were 11.8 °C, 103.5%, 7.38, and 32.0 g L−1, respectively. Fish fed plant-based feed without KM were lighter (p 0.05) to the control and 5% KM plant-based groups, with KM increasing feed intake (p

Development of healthy synbiotic corn-based snack: Nutritional composition and effect of agave fructan-alginate coating on survival of Lactobacillus acidophilus - Valeria Castillo-Escandón; Gabriela Ramos-Clamont Montfort; Alma Rosa Islas Rubio; Jolanta E. Marszalek; Rodrigo Subiría-Cueto; Silvia Fernández Michel (Journal of Cereal Science, 2023)

Dirofilaria immitis in pet dogs from the metropolitan area of the Colombian Caribbean - Maria A. Badillo-Viloria; Ignacio García-Bocanegra; Rodrigo J. de Lavalle-Galvis; Remigio Martínez; Steffania de la Rosa-Jaramillo; Adriana Castillo-Castañeda; Juan D. Ramírez; David Cano-Terriza (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Expression and localization of vascular endothelial growth factor and its receptors in the pig uterus during peri-implantation and determination of the in vitro effect of the angiogenesis inhibitor SU5416 on VEGF system expression - Rodrigo González López; David Alejandro Contreras Caro del Castillo; Griselda Valdez Magaña; Rosa Elena Sarmiento Silva; Francisco Ernesto Martínez Castañeda; María Elena Trujillo Ortega (Theriogenology, 2023)

Is adenosine deaminase (ADA) activity in saliva and serum a more accurate disease detection tool than traditional redox balance parameters in early-lactating dairy cows? - Cristina Castillo; Joaquín Hernandez; Juan Sotillo; Rodrigo Muiño; Jose L. Benedito; Ana Montes; Rafael Arana; Marta Matas-Quintanilla; Cándido G. Panizo; Ana María Gutiérrez Montes (Veterinary Research Communications, 2023)
Enzyme adenosine deaminase (ADA) is a marker of inflammation in domestic animals, but it is unclear whether it is a reliable marker of oxidative stress, especially in the transition period in dairy cows. This study aims to assess if ADA and redox status measurements in saliva provide the same utility to detect disease condition as that obtained from serum. Sixty-eight multiparous Holstein cows, between 2 and 3 weeks postpartum were selected. Five study groups were established: control (healthy), and cows with ketosis, mastitis, laminitis, and metritis. The parameters measured were ADA activity, total oxidants (TOS), antioxidants (TAC), and OSi ratio. Regarding redox status, no significant differences arise in both saliva and serum being the correlations negative and not significant. In saliva, ADA activity in healthy cows differs from those with pathological processes, having the lowest activities. In serum, ADA activity is similar in the healthy and ketosis cows, showing the lowest activities meanwhile animals with mastitis, laminitis, or metritis have significantly higher activities. In conclusion, the measurement of ADA activities and redox status in saliva does not give consistent results, being preferable to measure them in serum during the transition period.

Volatile organic compounds measured by proton transfer reaction mass spectrometry over the complex terrain of Quintero Bay, Central Chile - Rodrigo J. Seguel; René Garreaud; Ricardo Muñoz; Deniz Bozkurt; Laura Gallardo; Charlie Opazo; Héctor Jorquera; Lucas Castillo; Camilo Menares (Environmental Pollution, 2023)

Tpeak—Tend, a novel electrocardiographic marker in cats with hypertrophic cardiomyopathy—a brief communication - Rodrigo Franco Bastos; Giovana Lais Ruviaro Tuleski; Luisa Fernanda Castillo Franco; Marlos Gonçalves Sousa (Veterinary Research Communications, 2023)

Heat flow modelling of the Punta del Este Basin (offshore Uruguay) and its correlation with structural crustal domains - Rodrigo Novo; José Alexandre de Jesus Perinotto; Maria Gabriela Castillo; Bruno Conti (Tectonophysics, 2023)

Phylogeographic origin authentication of Araucaria araucana (Mol.) K Koch seedlings through the application of spectroscopy techniques in different infrared ranges and chemometric methods - Macarena Rojas-Rioseco; Rosario del P. Castillo; Jorge González-Campos; Roberto Ipinza; M. I. Sanhueza; Rodrigo Hasbún (New Forests, 2023)

First evidence of multiple paternity in the blue shark ( Prionace glauca ) - Sofía Armada‐Tapia; José Leonardo Castillo‐Geniz; Nelva Victoria‐Cota; Luis Rodrigo Arce‐Valdés; Luis Manuel Enríquez‐Paredes (Journal of Fish Biology, 2023)
Multiple paternity (MP) is defined as the behaviour in which females successfully mate with multiple males leading to offspring from different sires within the same litter. MP seems to be frequent and an evolutionary advantage in elasmobranchs. Here the authors report for the first time the occurrence of MP in the cosmopolitan blue shark Prionace glauca L. The evidence, gathered via microsatellite genotyping of pregnant females and their embryos, suggests that MP is very frequent in this species. Knowledge of MP in P. glauca should help describe more precisely its reproductive biology and contribute to the management of its populations.

Disentangling Environmental, Economic, and Technological Factors Driving Scallop (Argopecten purpuratus) Aquaculture in Chile - José Bakit; Gonzalo Álvarez; Patricio A. Díaz; Eduardo Uribe; Rodrigo Sfeir; Sebastian Villasante; Tomas Gabriel Bas; Germán Lira; Hernán Pérez; Andrés Hurtado; Raúl González-Ávalos; Jose Castillo-Venenciano (Fishes, 2022)
The boom-and-bust trajectory of the Argopecten purpuratus industry in Chile shows the progression from resource extraction (fishing) to production (aquaculture). This paper analyses the effects of environmental, economic, and scientific–technological factors. The influence of each factor on scallop production in Chile was reviewed for the period between the 1980s and 2020. The evaluation of the effects allows the visualisation of the industry’s productive evolution and reveals the current challenges. The occurrence of abrupt environmental disturbances, commercialisation under imperfect market configurations, and public and private efforts in scientific and technological advances have acted favourably on scallop production. However, an industry mainly focused on prices and high production volumes did not devote much effort to develop low-cost climate-resilient technologies. Today, economic challenges must be addressed by helping to reduce production costs and add economic value to products and by-products. Our results show that the industry must focus on low-cost technologies, the use of renewable energy, and the circularity of its processes. The environment ensures the capture of natural seeds and their adaptation to climate change. These challenges must not lose sight of the emerging effects of the COVID-19 pandemic.

Mapping Potential Toxic Elements in Agricultural and Natural Soils of the Piedemonte Llanero in Colombia - Juan Manuel Trujillo-González; Marco Aurelio Torres-Mora; Marlon Serrano-Gómez; Edgar Fernando Castillo-Monroy; Raimundo Jiménez Ballesta; Jesús Rodrigo-Comino (Water, Air, & Soil Pollution, 2022)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Precipitation of Heavy Metal Ions (Cu, Fe, Zn, and Pb) from Mining Flotation Effluents Using a Laboratory-Scale Upflow Anaerobic Sludge Blanket Reactor - Manuel José Leal-Gutiérrez; Rodrigo Cuéllar-Briseño; Andrei M. Castillo-Garduño; Marisela Bernal-González; Ángel Enrique Chávez-Castellanos; Julio Alberto Solís-Fuentes; María-del-Carmen Durán-Domínguez-de-Bazúa; Enrique Rodolfo Bazúa-Rueda (Water, Air, & Soil Pollution, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Contrasting responses of cluster roots formation induced by phosphorus and nitrogen supply in Embothrium coccineum populations from different geographical origin - Ariana Bertin-Benavides; Luisa Bascuñán-Godoy; Carlos Henríquez-Castillo; Mabel Delgado; Carlos F. Burgos; Catalina Mardones; Andrea Ávila-Valdés; Francisco Valdebenito; Soraya Bravo; Rafael Rubilar; Rodrigo Hasbún; Alejandra Zúñiga-Feest (Plant and Soil, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Fractional-Flow Theory for Non-Newtonian Surfactant-Alternating-Gas Foam Processes - Rodrigo O. Salazar Castillo; Sterre F. Ter Haar; Christopher G. Ponners; Martijn Bos; William Rossen (Transport in Porous Media, 2020)
Foam can improve sweep efficiency in gas-injection-enhanced oil recovery. Surfactant-alternating-gas (SAG) is a favored method of foam injection. Laboratory data indicate that foam can be non-Newtonian at low water fractional flow f w , and therefore during gas injection in a SAG process. We investigate the implications of this finding for mobility control and injectivity, by extending fractional-flow theory to gas injection in a non-Newtonian SAG process in radial flow. We make most of the standard assumptions of fractional-flow theory (incompressible phases, one-dimensional displacement through a homogeneous reservoir, instantaneous attainment of local equilibrium), excluding Newtonian mobilities. For this initial study, we ignore the effect of changing or non-uniform oil saturation on foam. Non-Newtonian behavior at low f w implies that the limiting water saturation for foam stability varies as superficial velocity decreases with radial distance from the well. We discretize the domain radially and perform Buckley–Leverett analysis on each narrow increment in radius. Solution characteristics move outward with fixed f w . We base the foam model parameters and non-Newtonian behavior on laboratory data in the absence of oil. We compare results to mobility and injectivity determined by conventional simulation, where grid resolution is usually limited. For shear-thinning foam, mobility control improves as the foam front propagates from the well, but injectivity declines somewhat with time. This change in mobility ratio is not that at steady state at fixed water fractional flow in the laboratory, however, because the shock front in a non-Newtonian SAG process does not propagate at fixed fractional flow (though individual characteristics do). Moreover, the shock front is not governed by the conventional condition of tangency to the fractional-flow curve, though it continually approaches this condition. Injectivity benefits from the increased mobility of shear-thinning foam near the well. The foam front, which maintains a constant dimensionless velocity for Newtonian foam, decelerates somewhat with time for shear-thinning foam. For shear-thickening foam, mobility control deteriorates as the foam front advances, though injectivity improves somewhat with time. Overall, however, injectivity suffers from reduced foam mobility at high superficial velocity near the well. The foam front accelerates somewhat with time. Conventional simulators cannot adequately represent these effects, or estimate injectivity accurately, in the absence of extraordinarily fine grid resolution near the injection well.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Leading by listening, learning by doing: modeling democratic approaches to conservation leadership in graduate education - Karen A. Kainer; Citlalli López Binnqüist; Jonathan L. Dain; Belinda Contreras Jaimes; Patricia Negreros Castillo; Roldan Gonzalez Basulto; Edward A. Ellis; Hannah H. Covert; Rodrigo López Rodríguez; Irving Uriel Hernández Gómez; Fernando Melchor Contreras (Journal of Environmental Studies and Sciences, 2019)

Sex change in the dioecious palm Ceroxylon quindiuense (Arecaceae) - Blanca Martínez; María José Sanín; Luis Santiago Castillo; René López; Rodrigo Bernal (Ecology, 2018)

Differences in DNA methylation, DNA structure and embryogenesis-related gene expression between embryogenic and non embryogenic lines of Pinus radiata D. don - Soraya Bravo; Ariana Bertín; Aileen Turner; Francisco Sepúlveda; Paz Jopia; María José Parra; Rosario Castillo; Rodrigo Hasbún (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Woody plant invasions and restoration in forests of island ecosystems: lessons from Robinson Crusoe Island, Chile - Cecilia Smith-Ramírez; Rodrigo Vargas; Jessica Castillo; Juan Pablo Mora; Gisella Arellano-Cataldo (Biodiversity and Conservation, 2017)

Effects of cryopreservation on mitochondria of fish spermatozoa - Elías Figueroa; Iván Valdebenito; Andrea B. Zepeda; Carolina A. Figueroa; Kelly Dumorné; Rodrigo L. Castillo; Jorge G. Farias (Reviews in Aquaculture, 2017)
The development of sperm cryopreservation has enabled transcendental changes to occur in the reproductive biotechnology of both mammals and fish; it has become a basic tool for animal improvement. Nevertheless, these protocols cause damage to cell structure and physiology, altering sperm functioning due to cryo‐injuries during freezing and thawing. However, studies of the effects on the structural, functional and genomic stability of the mitochondria in fish spermatozoa during cryopreservation are still lacking. The object of this review was to analyse the effect of cryopreservation on mitochondrial metabolic pathways in fish spermatozoa. This effect is related with the bioenergy mechanism for flagellar movement during the activation of sperm motility. In teleost fish, the mitochondria may be cylindrical, spherical or irregular in shape and adhere in a helicoidal or conical pattern to the middle piece. The salmonidae have only a single mitochondrion, but this may vary in other species; the mitochondria provide the flagellum with energy during sperm motility, when sperm respiration is essential. The effects of cryopreservation can induce structural damage to the mitochondria, altering the biochemical process involved in ATP production and thus causing a reduction in sperm motility. Fragmentation damage to nuclear DNA and diminution in sperm motility is mainly associated with damage to the structure and metabolic functioning of the mitochondrion. A direct correlation exists between the mitochondrial membrane potential (transmembrane integrity, ∆ Ψ m ) and the motility and fertilizing capacity of the cryopreserved spermatozoa, confirming that this organelle is the energy nucleus of the spermatozoon and that the cessation or prolongation of motility and successful fertilization depend on the availability of ATP in the spermatozoa. Further works are need to incorporate biotechnology studies, at cell and molecular level, of the possible effects of cryopreservation on mitochondrial DNA , enzymatic or metabolic modifications of the citric acid cycle, and the oxidative phosphorylation process in the inner membrane, as well as studies of the mitochondrial ultrastructure. Thus, mitochondrial dynamics could be established as a potential target for therapeutic strategies.

Decadal trends in the pollinator assemblage of Eucryphia cordifolia in Chilean rainforests - Cecilia Smith-Ramírez; Rodrigo Ramos-Jiliberto; Fernanda S. Valdovinos; Paula Martínez; Jessica A. Castillo; Juan J. Armesto (Oecologia, 2014)